2000
DOI: 10.1046/j.1365-2168.2000.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of blood transfusion and postoperative infectious complications on prognosis after surgery for colorectal cancer

Abstract: Blood transfusion per se may not be a risk factor for poor prognosis after colorectal cancer surgery. However, the combination of perioperative blood transfusion and subsequent development of postoperative infectious complications may be associated with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
2
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(114 citation statements)
references
References 33 publications
6
100
2
6
Order By: Relevance
“…Similarly, development of postoperative infectious complications is also associated with enhanced systemic induction of inflammatory cytokines. Mynster et al [18] shows that a combination of perioperative blood transfusion and subsequent development of postoperative infectious complications may be associated with a poor long-term prognosis in patients after potentially curative resections for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, development of postoperative infectious complications is also associated with enhanced systemic induction of inflammatory cytokines. Mynster et al [18] shows that a combination of perioperative blood transfusion and subsequent development of postoperative infectious complications may be associated with a poor long-term prognosis in patients after potentially curative resections for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the postoperative complications were risk factors for the survival or disease recurrence in various types of malignancies 7, 8, 9, 10, 11, 12. Furthermore, some authors have shown that the immunological response against postoperative complications enhanced the viability of undetectable residual tumor cells after surgery, thereby increasing the risk of disease recurrence 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies [1][2][3][4][5][6][7][8][9] have demonstrated that the development of postoperative complications increased the risk of disease recurrence in various types of malignancies. Among surgical morbidities, infectious complications are the most frequent and directly related to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Among surgical morbidities, infectious complications are the most frequent and directly related to surgery. Some authors [5,9,10] have suggested that the immunological response against postoperative infection enhanced the viability of undetectable residual tumor cells after surgery, thereby increasing disease recurrence.…”
Section: Introductionmentioning
confidence: 99%